2016
DOI: 10.5204/ssj.v7i1.305
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap to first year health science: Early engagement enhances student satisfaction and success

Abstract: <p><em>Student academic success and positive satisfaction in first year health sciences programs is shaped by their transition experience. An introduction to core knowledge, study skills, and engagement with staff and students has historically been overlooked, but this has been newly recognised as a contributor to first year success, especially with mass higher education of students from diverse backgrounds. The University of South Australia ‘Preparing for Health Sciences’ workshop was designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…The workshops achieved the objectives outlined at the outset. While there were many findings reported (Thalluri, 2016), the results highlighted in this paper relate to the psychosocial and emotional impacts of the workshop on students. Three themes emerged, and these were Increased preparedness and confidence; Networking and friendships that enhanced support, and Reduced anxiety to study sciences.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The workshops achieved the objectives outlined at the outset. While there were many findings reported (Thalluri, 2016), the results highlighted in this paper relate to the psychosocial and emotional impacts of the workshop on students. Three themes emerged, and these were Increased preparedness and confidence; Networking and friendships that enhanced support, and Reduced anxiety to study sciences.…”
Section: Resultsmentioning
confidence: 81%
“…The findings relevant to the topic of this article were drawn from this larger study. The result of the 2015-2018 evaluation showed that the workshop "improved students' confidence and enthusiasm in starting university (56% pre-and 95% postworkshop), and 97% considered the workshop effective overall" (Thalluri, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selfassessments of confidence are frequently used in measurements of the effectiveness of transition programs (e.g. Abdullahi & Gannon, 2012;Boelen & Kenny 2009;Thalluri, 2016), as confidence is understood as a measure of selfefficacy, which has been widely linked to successful retention (Bandura, 1978;Lawrence, 2005). On a five-point Likert scale from 'not confident at all' to 'very confident', 43% of students selected the top two categories, which we interpret as a very favourable result.…”
Section: Resultsmentioning
confidence: 99%
“…Engagement with students is a highly valuable tool which can play a role in course completion (Hopper, 2016;Thalluri, 2016). Retention rates in science degrees tend to be poor (Lombardi, Hicks, Thompson, & Marbach-Ad, 2014), and student confidence and perceptions of science are often negative (Craker, 2006).…”
Section: Student Perceptions To Undergraduate Teachingmentioning
confidence: 99%